Inclusion of Halal Labels on Food Products from a Legal Perspective and its Implications for the Lives of Muslim Consumers in Indonesia - Dilla Ayuna; Rahmi Erwin (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2025)
The inclusion of halal labels on food products is one of the consumer protection efforts, especially for Muslims who are required to consume halal food according to their religious teachings. From a legal perspective in Indonesia, the provisions regarding halal labels are regulated in Law Number 33 of 2014 concerning Halal Product Assurance (UU JPH), which requires every product that enters, circulates, and is traded in the territory of Indonesia to be halal certified, unless stated otherwise. The method used in this study is normative juridical with data collection techniques through document studies. This obligation is not only normative, but also has a broad impact on the practices of production, distribution, and consumption of food products. The implications of this regulation are very significant, especially in guaranteeing the rights of Muslim consumers to obtain certainty and comfort in consuming products that are in accordance with religious values. In addition, the inclusion of halal labels also affects consumer trust, product competitiveness, and the growth of the national halal industry. This study aims to analyze the legal basis for the inclusion of halal labels, the implementation mechanism, and its impact on the social and religious life of the Muslim community in Indonesia.